Efektifitas Video Pembelajaran Terhadap Pemahaman Siswa Pada Tata Cara Thaharah, Berwudhu, Tayammum, Mandi Waijib, Dan Sholat (Study Kasus Siswa Kelas 5 Dan 6 Di Sdn 14 Bokat) - Ni’mah Wahyuni; Ariyanti Ariyanti; Sri Yanti S Ja'anah; Wahyu Putra Aditia; Siti Sa'ban Rahim (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Thaharah, Wudu, Tayammum, obligatory bathing and good and correct prayers. Because nowadays there is a lack of understanding that aspects of the afterlife are separate from worldly life or aspects of spiritual life are separate from physical life. So this is our obligation as presenters to use study methods and practice. Apart from that, this material can also increase students' knowledge from not knowing to knowing. We make students aware of how important Thaharah, Wudu, Tayamum, obligatory bathing and prayer are. Because this is aimed at their puberty period so that when they reach puberty the students will already know and will no longer be confused about the proper and correct procedures for purification and worship. This research is a type of research on developing children's knowledge. We recommend the results of this research in the form of methods in the form of theories, concepts, materials and procedures. Specifically presented descriptively and topically. The population in this study were female students at SDN 14 Bokat, Bukamog village, especially in grades 5 and 6, totaling 70 students. This research uses pictures or posters that are displayed in front of the class and will be explained and practiced by the speaker with a correct understanding of the material explanation. This abstract provides insight to lecturers and researchers in writing and formulating methods in scientific journal abstracts.